2017
DOI: 10.3892/etm.2017.4159
|View full text |Cite
|
Sign up to set email alerts
|

Influence of camel milk on the hepatitis C virus burden of infected patients

Abstract: Hepatitis C virus (HCV) infection represents a world health problem and no protective vaccine or effective drug currently exists. For economic reasons, many patients use traditional medicines to control the infection. In Egypt, camel milk is one of the traditional medicines widely consumed by patients infected with HCV. The present study aimed to evaluate the efficacy of camel milk in the treatment of patients infected with HCV. Whole camel milk from a local farm was administered to patients for 4 months (250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Furthermore, camel milk is suggested to exert a number of therapeutic activities ( Hailu et al., 2016 , Mihic et al., 2016 ). Numerous studies suggest that camel milk has distinct therapeutic benefits, such as anti-diabetic ( Korish, 2014 , Korish et al., 2015 , Mirmiran et al., 2017 ), anti-toxic ( Al-Asmari et al., 2017 , Khan, 2017 ), anti-viral ( el Agamy et al., 1992 , El-Fakharany et al., 2017 , Lee et al., 2016 ), antibacterial ( Cardoso et al., 2013 , Rahimi and Kheirabadi, 2012 , Soliman et al., 2015 ), anti-rheumatoid arthritis ( Arab et al., 2017 ), anticancer ( Ayyash et al., 2017 , Chen et al., 2014 , Korashy et al., 2012 ), and wound healing ( Ebaid et al., 2015 , Ebaid et al., 2017 ) activities. In addition, camel milk has been used for centuries in the Middle East, Asian and North African cultures as a natural remedy for many common health problems ( Agrawal et al., 2011a , Agrawal et al., 2011b , Al-Ayadhi and Elamin, 2013 , Ehlayel et al., 2011a , Ehlayel et al., 2011b , Mohamad et al., 2009 , Mohamed et al., 2015 , Shori, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, camel milk is suggested to exert a number of therapeutic activities ( Hailu et al., 2016 , Mihic et al., 2016 ). Numerous studies suggest that camel milk has distinct therapeutic benefits, such as anti-diabetic ( Korish, 2014 , Korish et al., 2015 , Mirmiran et al., 2017 ), anti-toxic ( Al-Asmari et al., 2017 , Khan, 2017 ), anti-viral ( el Agamy et al., 1992 , El-Fakharany et al., 2017 , Lee et al., 2016 ), antibacterial ( Cardoso et al., 2013 , Rahimi and Kheirabadi, 2012 , Soliman et al., 2015 ), anti-rheumatoid arthritis ( Arab et al., 2017 ), anticancer ( Ayyash et al., 2017 , Chen et al., 2014 , Korashy et al., 2012 ), and wound healing ( Ebaid et al., 2015 , Ebaid et al., 2017 ) activities. In addition, camel milk has been used for centuries in the Middle East, Asian and North African cultures as a natural remedy for many common health problems ( Agrawal et al., 2011a , Agrawal et al., 2011b , Al-Ayadhi and Elamin, 2013 , Ehlayel et al., 2011a , Ehlayel et al., 2011b , Mohamad et al., 2009 , Mohamed et al., 2015 , Shori, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Camel milk and its ingredients have been claimed to have significant in vitro and in vivo activity against cancer, jaundice, hepatitis B and C, diabetes, dropsy, tuberculosis, spleen problems, anemia, piles, food allergies, high cholesterol in the blood and asthma (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). One of these unique ingredients is the camel heavy-chain antibodies which have advantages because of their low molecular weight, while their light chains are absent; they should bind their antigen by one single domain, the variable domain of the heavy chain, which is referred to as "VHH", a nanobody of only about 12 to 15 kDa molecular weight allowing its access to small spaces not accessible for conventional antibodies [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The sandwich ELISA was carried out using the previously described method by El-Fakharany et al (2017) with modification [1]. Briefly, high binding ELISA microplates were coated with 50 µL of coating solution in duplicate manner (coating buffer; 3.03 g of Na 2 CO 3 mixed with 6.0 g of NaHCO 3 to make 1 L, pH 9.6) and MFGM protein samples from Safra and Wadha were added at a concentration of 2.2 µg/mL.…”
Section: Elisa Immunoassay Validation For Selected Mfgm Proteinsmentioning
confidence: 99%
“…Camel milk has been consumed for thousands of years because of its immense nutritional value and health benefits. Several studies have revealed that camel milk has a high concentration of immunoglobulins, serum albumin, lactoferrin, the hormone insulin, and other important ingredients [1][2][3]. Recently, camel milk has been utilized as medication for treating many diseases including gastrointestinal disorders, diabetes mellitus, food allergy, cancer, and hepatitis C and B [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation